Motor abnormalities as a putative endophenotype for Autism Spectrum Disorders - Esposito, Gianluca; Pasca, Sergiu (Frontiers in Integrative Neuroscience, 2013)
Autism spectrum disorders (ASDs) represent a complex group of behaviorally defined conditions with core deficits in social communication and the presence of repetitive and restrictive behaviors. To date, neuropathological studies have failed to identify pathognomonic cellular features for ASDs and there remains a fundamental disconnection between the complex clinical aspects of ASDs and the underlying neurobiology. Although not listed among the core diagnostic domains of impairment in ASDs, motor abnormalities have been consistently reported across the spectrum. In this perspective article, we summarize the evidence that supports the use of motor abnormalities as a putative endophenotype for ASDs. We argue that because these motor abnormalities do not directly depend on social or linguistic development, they may serve as an early disease indicator. Furthermore, we propose that stratifying patients based on motor development could be useful not only as an outcome predictor and in identifying more specific treatments for different ASDs categories, but also in exposing neurobiological mechanisms.